2021
DOI: 10.1093/eurheartj/ehab569
|View full text |Cite|
|
Sign up to set email alerts
|

AV junction ablation and cardiac resynchronization for patients with permanent atrial fibrillation and narrow QRS: the APAF-CRT mortality trial

Abstract: Aims  In patients with atrial fibrillation (AF) and heart failure (HF), strict and regular rate control with atrioventricular junction ablation and biventricular pacemaker (Ablation + CRT) has been shown to be superior to pharmacological rate control in reducing HF hospitalizations. However, whether it also improves survival is unknown. Methods and results  In this international, open-label, blinded outcome trial, we randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(124 citation statements)
references
References 27 publications
6
89
1
4
Order By: Relevance
“…The results of the APAF-CRT study, which was performed in severely symptomatic patients with permanent AF and within 1 year of HF hospitalization irrespective of LVEF, showed that AV node ablation combined with CRT is preferred. 67 , 68 In this study, patients with narrow QRS complex had a 62% lower risk for the combined endpoint of mortality, HF hospitalization or worsening of HF, and a 72% lower risk of all-cause mortality and HF hospitalization in the ablate and pace group when compared with the pharmacological rate control group. Forty per cent of the study patients had LVEF ≤35%.…”
Section: Introductionmentioning
confidence: 63%
“…The results of the APAF-CRT study, which was performed in severely symptomatic patients with permanent AF and within 1 year of HF hospitalization irrespective of LVEF, showed that AV node ablation combined with CRT is preferred. 67 , 68 In this study, patients with narrow QRS complex had a 62% lower risk for the combined endpoint of mortality, HF hospitalization or worsening of HF, and a 72% lower risk of all-cause mortality and HF hospitalization in the ablate and pace group when compared with the pharmacological rate control group. Forty per cent of the study patients had LVEF ≤35%.…”
Section: Introductionmentioning
confidence: 63%
“…In current guidelines, APT is only used as the ultimate option for patients who are unresponsive or intolerant to intensive rate and rhythm control therapy [1] . We analyzed the advantages, and disadvantages of different forms of APT [9][10][11][13][14][15][16] (Table III). Studies found that regular RVAP can improve immediate hemodynamics compared with irregular RVAP of the same heart rate [9] .…”
Section: Discussionmentioning
confidence: 99%
“…APAF-CRT study compared the e cacy of AVNA with biventricular pacing therapy and medical therapy. The results showed that AVNA with biventricular pacing therapy was superior to medical therapy in reducing the incidence of HF, shortening hospitalization, improving the quality of life, and reducing allcause mortality [13,14] . This study proved the e cacy of biventricular pacing but we should not ignore its disadvantages, including high incidence of nonresponse, high operative di culty, and high cost [15][16][17] .…”
Section: Discussionmentioning
confidence: 99%
“…Despite having rate-controlled permanent AF in both groups, the study showed improved functional outcomes with atrioventricular node ablation and CRT, with a potential survival advantage. 69 Given the small study size (n=133 with only 27 deaths), these results must be considered hypothesis generating, and additional confirmatory outcome studies are needed. These data do, however, support the idea that regularization of heart rate in HFrEF with AF may mediate some of the benefits of pulmonary vein isolation; using atrioventricular node ablation and CRT to achieve regularization of heart rate requires further study.…”
Section: Treatment Of Af In Hfrefmentioning
confidence: 99%